Sleeping Beauty Mouse Models of Cancer: Microenvironmental Influences on Cancer Genetics - Guimaraes-Young, Amy; Feddersen, Charlotte R.; Dupuy, Adam J. (Frontiers in Oncology, 2019)
The Sleeping Beauty (SB) transposon insertional mutagenesis system offers a streamlined approach to identify genetic drivers of cancer. With a relatively random insertion profile, SB is uniquely positioned for conducting unbiased forward genetic screens. Indeed, SB mouse models of cancer have revealed insights into the genetics of tumorigenesis. In this review, we highlight experiments that have exploited the SB system to interrogate the genetics of cancer in distinct biological contexts. We also propose experimental designs that could further our understanding of the relationship between tumor microenvironment and tumor progression.